Self-Adjustment in Middle Adulthood Nuns Who Had Mutations of The Work - Simamora, Ruminta; Br Sembiring, Ribka Kariani; Gea, Mey Carlin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
The research purpose is to see the self-adjustment of middle adulthood nun who had mutations of the work, so them keep loyal on their call, and how they overcome the problems that arose as the effect of the job mutation. This research is a qualitative and use in-depth interviews on five middle adulthood nun aged 30 to 50 years old. The research time spans from March 2023 to Juni 2024. The result shows the self-adjustment could become a supporting factor and a resisting factor as well. The nuns who easily adapted tend to receive the mutation and do the new job in affective way with maximal effort. In contrary, the nuns who cannot make self-adjustment easily will face difficulties on the new job and in turn will rejects the duty or even if she still takes the job, she will face difficulties and will not able to proceed maximally. The vows can influence of nun and can be main reason for her to receive the mutation and still stick to the call. The results of this research showed that two subjects had a self-adjustment capability while the three others having trouble and one of them had refused mutation.